Mobile communication : bringing us together and tearing us apart - Ling, Richard Seyler; Campbell, Scott W. (New Brunswick, N.J. : Transaction, 2012)
This book covers a wide range of topics. These include the replacement of co-present interaction with mediated contact and analysis of mobile-based cohesion and gender. The authors also explore the role of media choice and its effect on the quality as well as quantity of social cohesion. Other topics include mobile communication and communities of interest; and mobile communication, cohesion, and youth. This volume brings together scholars from around the world to consider how mobile communication both builds and destroys our sense of social cohesion. There is no question that uses of technology can lead to increased cohesion within personal communities. For example, this volume includes research on caravan couples in Australia, factory workers in China, young couples in Germany, citizens in Slovenia, and sports clubs in Ireland.
Includes bibliographical references and index.
Keywords: Mobile communication systems -- Social aspects; Interpersonal communication -- Technological innovations -- Social aspects; Communication and culture